DELINEATING THE MORAL DOMAIN IN MORAL PSYCHOLOGY. - Berniūnas, Renatas (Problems / Problemos)
The aim of this paper is to review current debate about the moral domain in the moral psychological literature. There is some vagueness in respect to the usage of the very concept of 'morality'. This conceptual problem recently has been re-addressed by several authors. So far, there is little agreement, nobody seems to agree about how to delineate the moral domain from other 'non-moral' normative domains. Currently, there are several positions that disagree about the scope of morality, ranging from complete monists to complete pluralists. The paper will review these positions and will tentatively suggest further directions to test their claims. At this moment, there is no decisive evidence for either position.